(untitled) (Architecture Image Studies, 2023)
This study discusses the methods and special techniques for restoration to rebuild, renovate and reusing Khan Old Borsa (ÇİFTEHAN) at Diyarbakir_Turkey, by shining a light on a similar project (Khan Al Wakala) built in the same era almost been implemented and the mechanism followed during implementation The research aims to study and evaluation of Khan Al Wakala project in Palestine, which was restored to arrive at a clear methodology for restoration in order to achieve excellence in the areas of restoration and preservation of architectural historic buildings and areas of value, and improved optical image of the historical areas affected by the war or as a result of neglect in the city of Diyarbakir.